El militante total - Giaime Pala (Cahiers de Civilisation Espagnole Contemporaine)
This paper analyses the characteristics that made up not just the work but the political identity of the clandestine militant of the Unified Socialist Party of Catalonia (PSUC) during the Franco years. Namely, and through a methodological approach that combines social history and historical sociology, studying language, morals, political education and the mode of conceiving militancy from activist of PSUC such as essential elements to understand why PSUC became the stronger party of the opposition to the dictatorship in Catalonia.